Integrated And Holistic Education System As Fundamental Approach Towards Quranic Generation Outcome - Zetty Nurzuliana Rashed; Ab Halim Halim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Necessities towards integrated education system based upon aqli and naqli knowledge assimilation have a significant impact in moldings studentsâ€™ character and personality towards understanding al-Quran and consequently produces Quranic generation. The holistic and integrated education system becomes the basis to form the Quranic generation.Â Quranic generation as mentioned refers to a generation that understands religion and is not being enfolded with false interest towards wealth and possessions. This generation needs to be guided by al-Quran and being educated with the value and inspiring character as contained in the teachings of Islam. This study discussed the generation who can be the asset in building a civilization that can live the Islamic spirituality dynamically and positively. This generation will deal with changes that happen in our society based on human development and the spirit of Islam. It corresponds to the main purpose of Islamic education to bore human that is obedient towards Allah SWT. This paper could inspire and encourage curriculum developers, school founders, and administrators in striving for the academic excellence of Muslim education by providing a clearer picture of the concept of the Integrated Holistic Islamic system and its application.Kebutuhan terhadap sistem pendidikan terpadu berbasis asimilasi pengetahuan aqli dan naqli berdampak signifikan dalam membentuk karakter dan kepribadian siswa menuju pemahaman al-Qur'an dan akibatnya menghasilkan generasi al-Qur'an. Sistem pendidikan yang holistik dan terintegrasi menjadi dasar untuk membentuk generasi Al-Qur'an. Generasi Al-Qur'an sebagaimana disebutkan mengacu pada generasi yang memahami agama dan tidak diliputi oleh minat yang salah terhadap kekayaan dan harta benda. Generasi ini perlu dibimbing oleh al-Quran dan dididik dengan nilai dan karakter inspiratif yang terkandung dalam ajaran Islam. Kajian ini membahas tentang generasi yang dapat menjadi aset dalam membangun peradaban yang mampu menghayati spiritualitas Islam secara dinamis dan positif. Generasi ini akan menghadapi perubahan yang terjadi dalam masyarakat kita berdasarkan pembangunan manusia dan semangat Islam. Hal ini sesuai dengan tujuan utama pendidikan Islam untuk melahirkan manusia yang bertaqwa kepada Allah SWT. Makalah ini dapat menginspirasi dan menyemangati para pengembang kurikulum, pendiri dan pengelola sekolah dalam memperjuangkan keunggulan akademik pendidikan Islam dengan memberikan gambaran yang lebih jelas tentang konsep sistem pendidikan Islam yang terpadu dan penerapannya.